Investment analysis and portfolio management: readings from British publications - Taylor, Basil (London: Elek Books, 1970)
This book is the first collection of 'readings' of British articles in the field of portfolio investment. It provides a fairly comprehensive range of background reading for those who are professionally engaged in portfolio investment work in the United Kingdom.
Includes index.
rua 07/03/17
Loans
Keywords: Securities; Investments; Portfolio management; Investment analysis; Great Britain